Espiritualidade indígena: um estudo bibliográfico da tribo Wari (Pacaás Nova) no município de Guajará-Mirim-Rondônia - Silva, Talita Façanha da (2012)
This research presents a bibliographical study regarding the spirituality of the indigenous Native-Americans, the Wari Pacaás, located in the city of Guajará-Mirim, in the state of Rondônia. The research will address the history of this people culture, spiritual locations and ritual practices of ancient customs. The practice of funerary cannibalism was very strong; the Wari Pacaás Nova did this ritual to preserve the memories of their ancestors. In their ancient traditions, the Wari Indians had a strong connection with nature, however, one of the factors that most influenced their beliefs was the arrival of Christian missionaries. When these missionaries arrived, they began the process of converting the Wari to Catholicism. The process of converting the Wari took a long time. At the time the Wari Pacaás were very resistant to change, but due to the persistence of the missionaries, the Wari eventually converted; some of the Natives came believe in the God of the missionaries. The missionaries said that the processes of the shaman rituals in curing some diseases were of evil nature. To the Wari, the shaman was a represented by the spirits of ancestors or animals - the Wari believed that these spirits came to heal or reveal something. This briefing is intended to demonstrate the strength of the Wari in the context of Indian spirituality as a factor integrating the culture and life of these peoples.